Manajemen Peserta Didik dalam Peningkatan Kedisiplinan Siswa SMP Islam Al-Ulum Terpadu Medan - Rahmat Efendi (Harmoni Pendidikan : Jurnal Ilmu Pendidikan, 2024)
The research that has been conducted is entitled "manajemen peserta didik dalam peningkatan kedisiplinan siswa SMP Islam Al-Ulum Terpadu Medan", which is the background that the lack of student discipline during school hours starts from entering the school bell to the school bell to the school bell to go home from school. The lack of student discipline has the potential to have a negative impact, both academically and in daily life. The research method used is a case study with a qualitative approach. Data were collected through observation, indepth interviews with principals and analysis of documents related to disciplinary polices and procedures in schools. The results pf the study show that effective student management, including the establishment of clear rules, giving awards to student discipline ada teachers is an example for student. The conclusion of this study is that the application of structured student management can be an effective solution in overcoming discipline problems in schools.